2017
DOI: 10.2503/hortj.mi-159
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Research on Fruit Color Traits of the Bitter Gourd (<i>Momordica charantia</i> L.)

Abstract: The objective of this study was to determine the genetic model of fruit color in the bitter gourd (Momordica charantia L.). Six generations (P 1 , P 2 , F 1 , F 2 , BCP 1 , and BCP 2 ) in the hybrid set "MS 41 × MS 47" were used to estimate the genetic effects via generation mean analysis (GMA). The fruit color of the F 1 population was green implying the green color was dominant over the white color. The fruit color of the F 2 population showed a continuous distribution from white to dark green indicating thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Several studies have shown that the green fruit color is monogenically dominant over the white fruit color ( Srivastava and Nath, 1972 ; Hu et al, 2002 ; Dalamu et al, 2012 ). However, a more recent study indicated that this trait is controlled by quantitative genes ( Huang and Hsieh, 2017 ). Bitter gourd fruit has either a smooth or a distinct warty exterior, and has broken or continuous ridges.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the green fruit color is monogenically dominant over the white fruit color ( Srivastava and Nath, 1972 ; Hu et al, 2002 ; Dalamu et al, 2012 ). However, a more recent study indicated that this trait is controlled by quantitative genes ( Huang and Hsieh, 2017 ). Bitter gourd fruit has either a smooth or a distinct warty exterior, and has broken or continuous ridges.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies carried on pericarp color in horticultural plants. The genetic model of fruit color in bitter gourd was found to be a quantitative model through generation mean analysis; green is the dominant trait to white [ 2 ]. Gene mapping of pericarp color in wax gourd showed that the trait was controlled by one single gene; dark green color was dominant over yellow color, and the locus was located on chromosome 5 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results confirmed earlier report of Hu et al (2002) who explained fruit colour was controlled by one pair of nuclear gene with white recessive and green dominant in nature. In contrary, immature fruit colour in bitter gourd shows continuous distribution from white to dark green pointing this trait was controlled by quantitative genes (Huang and Hsieh 2017). The inheritance of seed coat colour was studied in cross DBGS-54 (Black seed) × DBGS-2 (Brown seed), all the progenies in F 1 bore light black seeds (Table 2).…”
Section: Resultsmentioning
confidence: 99%